Upaya Guru PAI dalam Mengatasi Kesulitan Membaca Al-Qur’an Siswa di SMP Negeri 1 Sampang Kabupataen Cilacap - Almahammah, Thammara; Hermawan, M.A. (Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the efforts made by Islamic Religious Education teachers in overcoming the difficulties of reading the Qur'an of students at SMP Negeri 1 Sampang. This research uses a descriptive qualitative approach with the type of field research. The data collection techniques used are observation, interview, and documentation. The informants in this study were the Principal, PAI Teacher, and Students of Class VII F, VIII D, IX A, and IX H. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed that PAI teachers at SMP Negeri 1 Sampang have made several efforts to overcome students' difficulty reading the Qur'an, namely: (1) Peer Tutor Program which is proven effective in creating a comfortable learning atmosphere and changing the influence of peers to be positive, (2) Extracurricular Reading and Writing Al-Qur'an (BTA) which is directed for students with basic difficulties in reading Al-Qur'an, (3) Practicing the science of tajweed practically through demonstration and practice, (4) Giving advice and motivation consistently, (5) Habituation of reading short surahs at the beginning of every PAI lesson